Effect of extrusion technique on antinutritional factors of sorghum-soya blends - T V, ARUN KUMAR; MANI, INDRA; PRAMOD, A; SAMUEL, D V K; JHA, S K; SAHOO, P K; SINHA, J P; KAR, ABHIJIT (The Indian Journal of Agricultural Sciences, 2023)
Response surface methodology was used to assess the effect of soya level (10-30%), feed moisture content (12-20% w.b.), barrel temperature (110-150Â°C) and screw speed (250-450 rpm) on trypsin inhibitor activity (TIA),phytic acid (PA) and tannin content of the sorghum [Sorghum bicolor (L.) Moench]-soya blends. Results showed that incorporation of soybean [Glycine max (L.) Merr.] increased antinutritional factors in the feed formulation butextrusion cooking considerably reduced these factors in the extruded snack. The extent of reduction being up to 96% in TIA and 57% in PA and tannin content. Second-order polynomial model showed that soya level and barrel temperature significantly (P